DishHunt: search for restaurants based on dish preference - Bustaman, Amiirrullah (2025)
DishHunt is a mobile application developed to promote food tourism in Kelantan by connecting tourists with local food vendors through dish-based restaurant searches. The project addresses the challenge faced by travelers in discovering authentic traditional cuisines due to the lack of centralized, reliable platforms. Built using the Android platform with PHP, MySQL, and XAMPP for backend support, the app allows users to search for restaurants by dish names, navigate through Google Maps, read reviews via Google Reviews, and view vendor promotions. Vendors, in turn, can update promotions, manage menus, and maintain their profiles. The application was developed using the Mobile Application Development Life Cycle (MADLC), ensuring a structured and efficient approach. The system enhances user experience, supports local businesses, and helps preserve culinary heritage. Despite limitations such as Android-only availability and reliance on internet connectivity, DishHunt presents a promising tool for enhancing cultural engagement and economic growth through food tourism in Kelantan.